Analysis of Tengkorak Londa Film Perception on Ammank Ameta Youtube Channel - Agimnastiar, Muhammad; Adiprabowo, Vani Dias (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
This research aims to analyze perceptions of the film "Tengkorak Londa." There is a lack of in-depth research regarding audience responses to horror films on digital platforms, and researchers want to know how audiences respond to these films. The research method used is descriptive qualitative with a focus on audience comments. Data is collected through observation and documentation. The research results showed that most viewers responded positively to this film but also provided criticism regarding the use of language, acting quality, visuals, introduction to local culture, and message delivery. Hopefully, this research will contribute to the development of communication science and become a reference source for policymakers.